The World of Honor and Shame in the New Testament: Alien or Familiar?. (February 2019) - Patterson, Colin
During the last sixty or more years, analysis of the New Testament which draws on the social sciences of cultural anthropology and sociology has made great strides in elucidating the cultural assumptions behind many scriptural texts. Prominent among its themes has been the idea that the biblical world can be understood as reflecting a Mediterranean culture with the core values of honor and shame. This, it has been argued, stands in sharp contrast to modern western societies. However, more recent work on the New Testament which exploits research in cognitive science/psychology suggests that it can provide a helpful corrective and complement to anthropological and sociological approaches. In line with this work, the present essay will apply the psychological analysis of social dominance hierarchies to the theme of honor-shame in order to fill out the picture painted by the social-scientific approach and, in doing so, seek to highlight continuities between New Testament and modern cultures. It will conclude by suggesting a reason why it has been the case that scholars employing social-scientific criticism have shown less awareness of these continuities.